Lifetime-based fault tolerant strategy for three-level hybrid ANPC inverters - Hwang, Jun Ho; Halabi, Laith M.; Ko, Youngjong; Lee, Kyo Beum (Journal of Power Electronics, 2023)
This paper presents a fault tolerant control that aims at improving the reliability of three-level hybrid ANPC inverters. Since the hybrid ANPC inverter consists of Si devices and SiC devices have a higher output quality and lower power losses, it has been considered in various power conversion industries. However, there still are concerns over its reliability since employing many power devices increased the risk of failure. Furthermore, the inverter is composed of a switching device and a DC-link capacitor, which mainly determine the reliability of the system. As one of the strategies to improve reliability, fault tolerant control methods have been intensively studied. However, applying the fault tolerant control increases the power losses of the switching device or the DC-link capacitor, which leads to earlier second failures. This paper proposes a lifetime-based fault tolerant strategy considering the remaining useful lifetime of the power device and DC-link capacitor, which increases the lifetime of the whole system. The validity and effectiveness of the proposed fault tolerant control method are verified through simulation and experimental results.
Keywords: Capacitor lifetime; Dc-link; Fault-tolerant; Fault-tolerant strategy; Faults tolerant controls; Hybrid ANPC; Reliability improvement; Switching loss; Three-level; Three-level inverters; Capacitor lifetime; Fault tolerant; Hybrid ANPC; Reliability improvement; Switching losses; Three-level inverter